Comparison of Tear Osmolarity in Rheumatoid Arthritis Patients With and Without Secondary Sjogren Syndrome. Issue 7 (July 2017) - Ng, Alex L. K.; Choy, Bonnie N. K.; Chan, Tommy C. Y.; Wong, Ian Y. H.; Lai, Jimmy S. M.; Mok, Mo Yin
Abstract : Purpose: To compare tear osmolarity (TO) and other dry eye parameters in rheumatoid arthritis (RA) patients with or without secondary Sjogren syndrome (sSS). Methods: Consecutive patients with RA were divided into a sSS group and no-sSS group using conventional diagnostic criteria by rheumatologists using symptomatology, Schirmer test score, and anti-Ro or anti-La autoantibody status. The TO, Ocular Surface Disease Index, dry eye disease (DED) parameters [such as tear breakup time (TBUT) and corneal staining score] and the systemic inflammatory markers [erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP)] were compared. Correlation analyses between TO and the DED parameters and inflammatory markers were also performed. Results: A total of 42 cases with mean age 54.8 ± 12.3 were included, with 12 patients (29%) having sSS and 30 (71%) without sSS. TO was increased in both groups (329 ± 20 and 319 ± 25 mOsm/L, respectively), but no statistically significant difference was found between the 2 groups ( P = 0.126). RA with sSS had significantly shorter TBUT, higher corneal staining score, and ESR CRP levels ( P < 0.05). TO did not correlate with the Schirmer test score, but had significant positive correlations with age, corneal staining score, ESR, and CRP levels, and a significant negative correlation with TBUT. Conclusions: TO was increased in RA patients with or without sSS. There was no significant correlation between TO and the Schirmer test score, and the physician could not use TO to diagnose sSS. However, TO correlated well with both DED parameters (TBUT and corneal staining score) and systemic inflammatory markers (ESR and CRP).